Konflik kerja-keluarga dalam kalangan pensyarah: satu tinjauan - Chew Abdullah, Nor Azimah (Universiti Teknologi Malaysia, 2016)
The main objective of this study was to explore the relationships between work-family conflict, job involvement and family involvement among lecturers from the higher education institution in the northern region of Malaysia, who had child under the age of seventeen and below.The sample size was 151 respondents.Respondents were later classified into 97 male lecturers (64.2%) and 54 female lecturers (35.8%).Data was collected using questionnaires. Data analysis was done using descriptive statistics, t-test, Pearson correlation and regression.The Pearson correlations showed that job involvement and family involvement were not highly correlated with work-family conflict.The t-test also showed no significant differences between male and female lecturers in work-family conflict. Job involvement and family involvement do not explained the variation in work-family conflict.